THE WORLD ALMANAC AND BOOK OF FACTS 2019 - Janssen, Sarah( 1982-)
Presents a reference with comprehensive facts and statistics on current events, people, and the countries of the world, along with original articles on recent issues and topics ranging from the Obama presidency to the global economic crisis.